An Examination of Noncompleted Sexual Offences, Offenders' Perceptions of Risks and Difficulties and Related Situational Factors. (November 2022) - Leclerc, Benoit; Reynald, Danielle; Wortley, Richard; Cook, Alana; Cale, Jesse
Objectives: The current study aims to generate insights from sexual offenders on noncompleted sexual offences, that is, on offences that were stopped or discouraged. Methods: Using a sample of sexual offenders who initiated a sexual offence but were stopped or discouraged in action, which we refer to as noncompleted offences, we first examine which and how situational factors and internal states may affect their assessment of risks of apprehension and difficulties in this context. Second, we examine whether situational factors, internal states as well as perceived risks and difficulties can predict offence noncompletion. Linear and logistic regression models were estimated based on the type of offence (noncompleted sexual offences against women or children). Results: Main findings indicate that victim physical resistance is critical for how sex offenders are perceiving difficulties related to offending against women. The presence of a person nearby and victim resistance are predictive of noncompletion of sexual offences against children. Conclusion: This is a critical line of research because knowledge on the factors and circumstances that can discourage or stop offenders from committing crimes can be used by scholars and practitioners to think of prevention initiatives to reduce opportunities of crime.